2020
DOI: 10.1159/000504515
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Safety of Biweekly and Monthly Nivolumab in Patients with Metastatic Renal Cell Carcinoma and Dialysis: Three Case Reports and Literature Review

Abstract: Nivolumab is a fully human immunoglobulin G4 programmed death-1 (PD-1) immune checkpoint inhibitor antibody that selectively blocks the interaction between PD-1, which is expressed on activated T cells, and its ligands PD-L1 and PD-L2, which are expressed on immune cells and tumour cells. Patients with severe renal dysfunction and haemodialysis are not enrolled in clinical trials. However, in daily clinical practice, we have patients with metastatic renal cell carcinoma (mRCC) and end-stage renal disease (ESRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…3 Currently, there are few published cases of ICI use in patients receiving dialysis. [4][5][6][7] We aimed to characterize cancer response rates and the incidence of overall and severe (grade 3/4) irAEs in nonselected patients undergoing dialysis receiving ICIs at Partners Healthcare.…”
Section: Safety and Efficacy Of Immune Checkpoint Inhibitors In Patiementioning
confidence: 99%
“…3 Currently, there are few published cases of ICI use in patients receiving dialysis. [4][5][6][7] We aimed to characterize cancer response rates and the incidence of overall and severe (grade 3/4) irAEs in nonselected patients undergoing dialysis receiving ICIs at Partners Healthcare.…”
Section: Safety and Efficacy Of Immune Checkpoint Inhibitors In Patiementioning
confidence: 99%
“…A clinical study investigating its safety and efficacy in metastatic patients with RCC and ESRD reported that progression free survival, OS, and the frequency of irAEs were not significantly different between the ESRD and non‐ESRD groups. 7 Five cases of nivolumab use in patients undergoing HD have been reported 4 , 8 , 9 , 10 showing good efficacy. During nivolumab treatment, the patient's disease no longer progressed for 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…На настоящий момент однозначно сложно делать выводы о прогнозе для пациентов с терминальной стадией ХБП на фоне иммунотерапии злокачественного новообразования. Необходимо проводить дальнейшие исследования в данной группе для получения более репрезентативных выборок и оценки прогноза в зависимости от гистологического типа опухоли [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: иммунотерапия и хроническая болезнь почекunclassified